riot321
Answered

If f(x)=4x3+3x2−5x+20 and g(x)=9x3−4x2+10x−55, what is (g−f)(x)?

A) 5x3−7x2+15x−75
B) 5x3+x2+5x+35
C) 13x3−x2+5x−35
D) −5x3+7x2−15x+75

Answer :

Answer:

Step-by-step explanation:

(g-f)(x) = 9x³ - 4x² + 10x - 55 - [ 4x³ +3x² - 5x + 20]

To remove the parenthesis, take - inside, multiply f(x) by -1

= 9x³ - 4x² + 10x - 55 -  4x³ - 3x² + 5x - 20  

Now, bring like terms together,

= 9x³ - 4x³ - 4x² - 3x² + 10x + 5x - 55 - 20

= 5x³ - 7x² + 15x - 75

Tig15

Answer:

the answer is C

Step-by-step explanation:

Other Questions